Studies on Anti-diabetic Activities in Flowers of Avaram, Senna auriculata (L.) Roxb. - Jose, Haritha; Yuvarani, T.; Suganthi, S.; Lakshmi, K.; Neelavathi, R.; Indurani, C. (International Journal of Economic Plants, 2022)
The research project on “Studies on anti-diabetic activities in flowers, leaves and barks of Avaram, Senna auriculata (L.) Roxb.” was carried out at Horticultural College and Research Institute for Women, Tamil Nadu Agricultural University, Tiruchirappalli during 2015–16. Avaram is used in the treatment of diabetes in Siddha and Ayurvedic medicines. The flowers, leaves and bark of Avaram were collected from Medicinal Park, Horticultural College and Research Institute for Women, Tiruchirappalli and Krishnagiri. The methanol extract of flowers exhibited high alpha-amylase inhibition compared to leaves and barks. The highest α-amylase inhibition was recorded in flowers at 40 µg ml-1 (86.2%) followed by 30 µg ml-1 (85.5%) with IC50 value of 21 µg ml-1. The highest inhibition was recorded in leaves of Avaram at 40 µg ml-1 (71.11%) followed by 30 µg ml-1 (69.25%) with IC50 value of 19 µg ml-1. The highest inhibition was recorded in the bark of Avaram at 40 µg ml-1 (64%) followed by 30 µg ml-1 (62.62%) with IC50 value of 22 µg ml-1. DPPH radical scavenging activity was found to be high in flowers compared to leaves and barks. The highest radical scavenging activity was recorded in flowers at 80 µg ml-1 (73.78%) sample followed by 100 µg ml-1 (73.32 %) with IC50 value of 55 µg ml-1. In GC-MS/MS analysis of flowers, the highest peak area was recorded for Myo-inositol 4-C- methyl (53.91 %) followed by resorcinol (20.71%). The anti-diabetic compounds include Myo-inositol 4-C methyl, resorcinol, polyphenols and sterols.